P-B31 Cohort profile: African Collaborative Center for Microbiome and Genomics Research (ACCME) Study. (January 2016) - Adebamowo, Sally; Dareng, Eileen; Famooto, Ayo; Odutola, Michael; Bakare, Rasheed; Adebamowo, Clement
Abstract : Background: Cervical cancer is the second commonest cancer in Africa. Much remains unknown about the prevalence and pathogenicity of human papilloma virus (HPV) types, mechanism of disease and there is a need for new biomarkers for screening programs. Methods: ACCME is a multicenter prospective cohort study of host germline, somatic and HPV genomics and epigenomics, and vaginal microenvironment; and their association with cervical cancer in 10, 000 HIV negative women in Nigeria. Data on demography, lifestyle, medical history, serum, germline DNA, HPV genotype and vaginal pH are collected at baseline and during follow- up visits every 6 months. Samples of exfoliated cervical cells are analyzed for high-risk HPV with Roche LINEAR ARRAY and vaginal bacterial composition and abundance are characterized by deep sequencing of barcoded 16S rRNA gene fragments (V4) on Illumina MiSeq platform. Colposcopy and biopsy are conducted on participants with clinical lesions and those with persistent high risk HPV infections. Results: By July 2015, ∼8500 participants had been enrolled unto the cohort. The mean (SD) age of the study participants at baseline was 40 (10) years. Most of the participants were married (76%), attended university (44%) and had professional jobs (37%). All the study participants have had vaginal sex, 17% have had oral sex and only 2% have ever had anal sex. We found 30% of the study participants were HPV positive and 70% were HPV negative. The mean (SD) vaginal pH in the study population was 5.2 (0.5). Further analyses to characterize high-risk HPV types and determine persistence are ongoing. Also, characterization of cervical cytokines and vaginal microbiome are underway. Conclusions: ACCME is a paradigm for translational research in biomarker discovery that addresses high impact public health challenges affecting women's health in Africa and the rest of the world.